Detection and Management of Adverse Drug Reactions Related to Antiretroviral Drugs among HIV/AIDS Patients in Kiambu Sub-County, Kenya (The East and Central African Journal of Pharmaceutical Sciences, 2018)
The objective of this study was to establish the detection, prevalence and management of various adverse drug reactions associated with antiretroviral drugs occurring in patients attending Comprehensive Care Centre (CCC) of Kiambu District Hospital. The study was a cross sectional survey where the patients included were those attending the CCC on a monthly basis. The results revealed that 65.2% of the patients had experienced symptoms suggestive of adverse drug reactions (ADRs). Of these, 67.2% did not associate the symptoms to the medicines they were taking but rather to the AIDS syndrome. The most prominent reaction was peripheral neuropathy at 0.395 (0.344-0.447 at 95% confidence interval) while the least common was hepatotoxicity. Whereas 71.5% could tell the frequency of the daily dosage, 92.1% did not know the names of the medicines they were taking but could describe them by shape and colour. There was a significant association between occurrence and reporting of ADRs and age (P
Keywords: Adverse drug reactions; occurrence; detection; management